2013
DOI: 10.1111/hsc.12057
|View full text |Cite
|
Sign up to set email alerts
|

Factors that promote and hinder joint and integrated working between health and social care services: a review of research literature

Abstract: This article reports the results of a review of the research evidence related to joint working in the field of adult health and social care services in the UK. It explores whether recent reforms to joint working have met the objectives set by policy‐makers. The review followed an established methodology: electronic databases were searched using predetermined terms, abstracts were screened against inclusion criteria, studies that met the criteria were read in full and assessed for inclusion and data were extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
284
1
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(310 citation statements)
references
References 38 publications
(121 reference statements)
9
284
1
8
Order By: Relevance
“…Several factors were identified that could help integration, many of which have also been reported elsewhere, 69,92 for example co-location of services and or/practitioners, 1,92,93 aligned administrative systems and financial arrangements; 41,[94][95][96] shared IT systems 97,98 and shared outcome indicators.…”
Section: Chapter 7 Discussionmentioning
confidence: 70%
“…Several factors were identified that could help integration, many of which have also been reported elsewhere, 69,92 for example co-location of services and or/practitioners, 1,92,93 aligned administrative systems and financial arrangements; 41,[94][95][96] shared IT systems 97,98 and shared outcome indicators.…”
Section: Chapter 7 Discussionmentioning
confidence: 70%
“…It is acknowledged in the literature that there are various approaches to integration and that no-one model is universally applicable (Curry and Ham, 2010) but that multiple factors contribute to its success.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The facilitators and barriers to integrated care and integrated team working being well documented (Hudson, 2006a; Hudson, 2006b; Morrow et al, 2005; Syson and Bond, 2010; Tucker, 2010Cameron and Lart, 2003;Cameron et al, 2012) with many of these appearing to reflect different dimensions of culture. Kodner (2002) described integration as a culture rather than structure:…”
Section: Literature Reviewmentioning
confidence: 99%
“…IRISS suggest that the 'emphasis should be on service integration rather than on organisational integration' (p. 10). Again, much of the research has focused on processes not outcomes and Cameron et al (2012) conclude:…”
Section: The Multi-disciplinary Environmentmentioning
confidence: 99%